Kritik Terhadap Metode Siklus Empiris Dalam Ilmu Administrasi Publik: Tinjauan Terhadap Perkembangan Ilmu Administrasi Publiok - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 2003)
ABSTRACT Contrast to the natural science, human being is both sulject and object of the rerearai the solid science. As the consequence, it is not enough to explain the behaviour of human being rising causal explanation only e.g. withoutfierther effort to understand and interpret it instil the stage of meaning (verstehen or hermeneutic). One of the instruments to do so is the empirical gdes. By using this approach, the author tries to explain the development of organisational theory as one of the branches in the administrative theory.